ANALISIS PERBANDINGAN SIFAT MEKANIS PIPA TEMBAGA AC BARU DAN BEKAS - R.N. Akhsanu Takwim; Kris Witono; Bambang Irawan (INFO-TEKNIK, 2018)
In the repair of the installation of air conditioners or refegeration are oftenfound referigeran (ACR) tube that must be replaced because the old copper tubeleaked on the connection. Replacement is done because the repair of the connectionby cutting and flaring the connection usually fails in the form of a tear on the flaredpart.The cause of flaring failure in the used air conditioner tube by testing themechanical properties and the microstructure of the material and compared with themechanical properties and the microstructure of the new tube material.Knowing thecauses of the failure can be searched for the prevention and repair solutions so thatthe old tube can be used without replacement.The tensile test results showed that the average ultimate strength of the usedACR copper tube has increase in strength of 18188.65 N/mm2 comparing with theultimate strength of the new copper tube which was only 14615.15 N/mm2.The microVickers test results show the same phenomenon from the tensile test results, wherethe hardness value of used ACR tube has 42.7 HV while the new ACR tube is 37.8HV.Microstructure testing with SEM shows the changing in grain structure from alongitudinal shape with a large enough grain size and tenuous in a new tube, to moreflat and dense longitudinal grain structure for used tube.